THE EFFECT OF ZEOLITE ON THE PERFORMANCES OF POST WEANING MICE (Mus musculus) - Pollung H. Siagian; Hotnida C. H. Siregar; Ronny Dasril (Institut Teknologi Bandung, 2006)
Zeolite is one kind of mining commodity that can be used in feed. Zeolite is used as molecule filter and ion exchange, so the usage of zeolite until certain level will increase protein efficiency and decrease cost efficiency. The main purpose of this research was to compare the effect of zeolite levels (0%, 3%, 6%, and 9%) in feed on the performances of post weaning mice (M. musculus), i.e. dry matter consumption of feed, protein consumption, daily weight gain, feed convertion, water and protein content of feces. Based on the analysis result, the usage of zeolite until 9% was highly significant (P